2018
DOI: 10.2139/ssrn.3266970
|View full text |Cite
|
Sign up to set email alerts
|

Installation of a Cancer Promoting WNT/SIX1 Signaling Axis by the Oncofusion Protein MLL-AF9

Abstract: Background: Chromosomal translocation-induced expression of the chromatin modifying oncofusion protein MLL-AF9 promotes acute myelocytic leukemia (AML). Whereas WNT/β-catenin signaling has previously been shown to support MLL-AF9-driven leukemogenesis, the mechanism underlying this relationship remains unclear. Methods: We used two novel small molecules targeting WNT signaling as well as a genetically modified mouse model that allow targeted deletion of the WNT protein chaperone Wntless (WLS) to evaluate the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Indeed, Eya1 overexpression immortalizes hematopoietic progenitor cells, and heterodimerization with Six1 augments this effect (26). Furthermore, two recent reports demonstrate a reduced LIC population in Six1 knockout or knockdown mouse cells expressing MLL-AF9 versus in a Six1 WT background (48,49). The unexpected observation that we see increased proliferation in the colony formation assay with MLL-AF9(E531R) could in part be due to increased expression of Hoxa7 ( Fig.…”
Section: Discussionsupporting
confidence: 52%
“…Indeed, Eya1 overexpression immortalizes hematopoietic progenitor cells, and heterodimerization with Six1 augments this effect (26). Furthermore, two recent reports demonstrate a reduced LIC population in Six1 knockout or knockdown mouse cells expressing MLL-AF9 versus in a Six1 WT background (48,49). The unexpected observation that we see increased proliferation in the colony formation assay with MLL-AF9(E531R) could in part be due to increased expression of Hoxa7 ( Fig.…”
Section: Discussionsupporting
confidence: 52%
“…MLL-AF9 is known to be a driver of acute myeloid leukemia (AML). Zhang et al confirmed that SIX1 was the target gene of leukemic initiating cells (LICs) confusion protein (MLL-AF9), and blocking WNT/SIX1 signaling by Wnt signaling inhibitors suppressed the progression of AML [61]. EYA1 and SIX1 are induced by MLL-ENL, EYA1 could immortalize hematopoietic progenitor cells, and SIX1 enhanced the transforming capacity of EYA1 [175].…”
Section: Hematologic Cellsmentioning
confidence: 99%
“…Furthermore, Zhang et al illustrated that SIX1 directly affected the expression activity of SIX1 and EYA1 in MLL-AF9. With the administration of WNT signaling inhibitors, WNT/ SIX1 signaling was disrupted, which delayed the progression of AML [61]. Monteiro et al proposed that the methylation of the SIX1 promoter could be an independent prognostic factor for overall survival in melanoma patients [201].…”
Section: Six1mentioning
confidence: 99%
“…Therefore, this study showed that the activation of the Wnt/β‐catenin signaling pathway is necessary for AML induction by HoxA9 and Meis1, as well as by KMT2A ‐ AF9 rearrangement. Moreover, the fusion protein KMT2A‐AF9 facilitates the accessibility of the Wnt transcriptional effector TCF‐4 to the transcriptional regulatory elements of SIX1 , a growth‐promoting homeobox gene, contributing to the growth of leukemic initiating cells (LICs) 60 …”
Section: Acute Myeloid Leukemiamentioning
confidence: 99%
“…Moreover, the fusion protein KMT2A-AF9 facilitates the accessibility of the Wnt transcriptional effector TCF-4 to the transcriptional regulatory elements of SIX1, a growth-promoting homeobox gene, contributing to the growth of leukemic initiating cells (LICs). 60 The oncogenic potential of other fusion proteins has also been linked to Wnt signaling activation in AML. 61 in RUNX1-RUNX1T1 AML.…”
Section: Chromosomal Abnormalities Fusion Genes and Chimeric Proteinsmentioning
confidence: 99%